PERSONAL HYGIENE AND ANTHELMINTIC CONSUMPTION IN PREVENTION OF ENTEROBIASIS AMONG PRIMARY SCHOOL CHILDREN - Ratna Muliawati; Mushidah Mushidah; Siti Musyarofah (Universitas Airlangga, 2020)
Background: Pinworm infection remains a global public health problem in Indonesia, with the highest prevalence in primary school–aged children. The government has made helminthiasis control efforts through annual deworming every six months, yet data on the enterobiasis prevalence and its risk factors are still limited. Purpose: This research aimed to determine the role of personal hygiene and anthelmintic or worm medicine consumption in the prevention of enterobiasis among primary school children. Methods: This research employed an analytic observational method with a cross-sectional design. The population used was primary school children in the Public Health Center (PHC) of Kaliwungu area, Kendal District, Central Java Province. The research sample was 150 students from first grade to third grade at 1 Primary Elementary School 1 Kutoharjo. The data sources were obtained from interviews of risk factors and perianal swab examinations. The data were analyzed by a chi-square test and multiple logistic regression. Results: The prevalence of pinworm infection among primary school children remains high (37.33%). The results of the multivariate analysis showed that there are three determinant variables of pinworm infections: not washing hands with soap before eating (p < 0.01; Prevalence Odds Ratio (POR) = 6.47; 95% Confidence Interval [CI] = 2.87 < POR < 14.59); not washing hands with soap after defecation (p = 0.01; POR = 3.36; 95% CI = 1.40 < POR < 8.05); and not consuming anthelmintic drugs within the past six months (p = 0.03; POR = 2.43; 95% CI = 1.08 < POR < 5.50). Conclusion: Hand washing habits and annual deworming are important factors to prevent pinworm infections.